Understanding the Consumer: AI-Driven Predictive Analytics and the Transformation of Purchasing Behavior - Jama, Iman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The digital era has revolutionized marketing from a product-centric to a customer-centric approach. Understanding consumer behavior is no longer an indulgence; it is a requirement. Artificial intelligence (AI), with its remarkable predictive analytics features, is a game-changing asset to companies. This article analyzes the implications of utilizing Artificial Intelligence Systems in predicting consumer behavior and its impact on business strategies. The method used in this study is an investigation of actual cases of firms that have effectively used this technology. Case studies were conducted on several companies that have successfully implemented this technology to understand the context of their implementation and the benefits they derived. This paper also addresses the benefits and drawbacks of AI for consumer behavior prediction and ways to overcome these obstacles. Results revealed that implementing AI Technology in forecasting customer behavior can significantly improve product individualization, enhance marketing tactics, and provide profound insights into consumer preferences. While AI’s potential in marketing is evident, it’s crucial to emphasize the need for more study to fully comprehend its long-term implications on consumer psychology and establish safeguards against biased algorithms.